First Resolution of Microlensed Images of a Binary-lens Event - Wu, Z.; Bensby, T. ; 0000-0003-3978-1409; Widmann, F. (Astrophysical Journal, 2024)
We resolve the multiple images of the binary-lens microlensing event ASASSN-22av using the GRAVITY instrument of the Very Large Telescope Interferometer (VLTI). The light curves show weak binary-lens perturbations, complicating the analysis, but the joint modeling with the VLTI data breaks several degeneracies, arriving at a strongly favored solution. Thanks to precise measurements of the angular Einstein radius θ E = 0.724 ± 0.002 mas and microlens parallax, we determine that the lens system consists of two M dwarfs with masses of M 1 = 0.258 ± 0.008 M ⊙ and M 2 = 0.130 ± 0.007 M ⊙, a projected separation of r ⊥ = 6.83 ± 0.31 au, and a distance of D L = 2.29 ± 0.08 kpc. The successful VLTI observations of ASASSN-22av open up a new path for studying intermediate-separation (i.e., a few astronomical units) stellar-mass binaries, including those containing dark compact objects such as neutron stars and stellar-mass black holes. © 2024. The Author(s). Published by the American Astronomical Society.